Hoff's Investigation of The Sandwich Panel with Honeycomb Core - Yassen, Muheeb; Brethee, Khaldoon (Anbar Journal of Engineering Sciences, 2022)
Recently, the use of sandwich panels has become increasingly important. This is due to its good mechanical properties and high strength-to-weight ratio. It is used in many fields, especially in aviation, construction and aerospace. It is necessary to know the behavior of the materials used, especially the free vibrations, to know the effect of external factors on the sandwich panels. The honeycomb core sandwich panel was studied. A model for analysis and modeling is proposed. A previous model was chosen for analysis and comparison. Hoff theory was applied to convert honeycomb sandwich panel into equivalent sandwich panel to facilitate the solution and save time. The limits were considered fixed on the one hand and moving on the other hand, and the ANSYS program was used to analyze and extract the results, and the results were compared and were promising and accurate, which proves to us the validity and accuracy of the proposed theoretical results